Design and Development of Documentary Video in Batam as Dark Tourism Promotion Media - Hendi Sama; Zulkarnain Zulkarnain; Felix Agusta Putra (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
Tourist destinations are zones that are directly designated and advertised as tourist destinations, and all tourism products are sold by a specific group of tourists who wish to visit a tragic place and know the meaning of the event. It is arranged. , happened in this place. The development of dark tourism can increase foreign tourist visits which can be used as an economy related to the government by attracting foreign tourists who want to provide foreign exchange for dark tourism, including remote areas. I can do that. The author uses the flow of literature study and subsequent problem-solving. This continues and is improved up to the implementation stage and ends at the dissemination stage. There are still many who don't understand how to attract tourists' attention from dark tourist destinations, whether it's shooting a film in the form of a vintage color gradation video with a frame, or using R&D using R&D. Check out the research flow by starting research and dividing the time, looking for stories about the place, and news about the ghost town of Batam calm and explore with the team of ghost hunters of Batam city. While exploring the ghost places of Batam City, unexpected things and events such as camera battery running low while recording, the crew being disturbed by ghosts, and things that are not nearby are crime scenes. Events that require you to bring safety equipment and lighting, as this is an unplanned event.